Examining future spatiotemporal changes in blue and green water using an enhanced SWAT model: A Jialing River basin case study - Mingyan Wu; Fuquan Ni; Yu Deng; Nan Jiang; Mengyu Zhu; Huazhun Ren; Ziying Yue; Yuxuan Wang (Ecological Indicators)
River basin water supplies are changing significantly as a result of global climate change. Therefore, it is crucial to examine the spatial and temporal variations of blue and green water (BW and GW) in future contexts. This research focuses on the Jialing River Basin, utilizing an enhanced Soil & Water Assessment Tool (SWAT) model alongside CMIP6 data, and selects representative years of dry-hot composite events through the Dry-Hot Magnitude Index (DHMI) to study the alterations in blue and green water across various future scenarios. The findings indicate that: (1) The enhanced CO2-SWAT model minimizes uncertainty in future projections and details alterations in blue and green water within these projections. (2) In the future, higher precipitation and temperature indicate a trend towards warmer and wetter conditions. Given these circumstances, the yearly fluctuations in blue and green water within the Jialing River Basin are anticipated to be more significant in the distant future than in the short future, with the majority of the basin’s blue and green water levels likely surpassing historical records. (3) Rising temperatures encourage plant growth, resulting in an earlier growing season; however, extremely high temperatures can hinder vegetation development, impacting the transformation and allocation of blue and green water within the basin. (4) In most areas of the basin, extreme heat and dryness lead to a notable shift from blue water to green water, linked to soil moisture buildup prior to drought conditions. Despite the suppression of vegetation activity due to elevated CO2 and high temperatures in future scenarios, increased vegetation growth demands in agricultural areas exacerbate soil water shortages and elevate future risks to water and food security. The findings provide scientific support for comprehensive water resource management of the Jialing River Basin and offer scientific references for water resource allocation and drought response under climate change in the basin.